A method for combined comprehensive utilization of germanium-rich lignite dressing and smelting

Through the combined process of ore dressing grading, catalytic oxidation treatment and nitric acid leaching treatment, the problems of low germanium dissolution rate and low organic matter utilization rate in germanium-rich lignite are solved, efficient germanium extraction and organic matter depolymerization are achieved, and efficient humic acid products are generated, reducing process costs and carbon emissions.

CN119530540BActive Publication Date: 2025-04-29CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510100358.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-29
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

In the existing recycling and utilization methods of germanium-rich lignite, the dissolution rate of germanium-rich lignite is low, the utilization rate of organic matter is low, the process flow is long, the energy consumption is large, the germanium recovery rate is low, the utilization rate of carbonaceous resources is low, and the carbon emission is high, which seriously restricts the development of the germanium-rich lignite extraction industry.

Method used

The combined process of ore dressing grading, catalytic oxidation treatment and nitric acid leaching treatment is adopted. The catalytic preoxidation treatment significantly improves the primary direct wet extraction rate of germanium, and reduces the amount of leaching agent and the heating leaching time, improves the activation and depolymerization of organic matter, and generates humic acid products with better structural characteristics.

Benefits of technology

The primary direct wet extraction rate of germanium is achieved to reach more than 80%, which significantly reduces the amount of leaching agent and heating leaching time, improves the activation and depolymerization of organic matter, produces efficient humic acid products, and reduces the overall process cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530540B_ABST
    Figure CN119530540B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for the combined comprehensive utilization of germanium-rich lignite beneficiation and smelting, which comprises the following steps: classification and crushing of germanium-rich lignite, catalytic pre-oxidation treatment, nitric acid leaching treatment, and recycling and separation and enrichment of germanium solution. The present invention realizes the activation and transformation of organic components in the germanium-rich lignite while realizing the separation and extraction of germanium from the germanium-rich lignite through a combined method of ore dressing, hydrometallurgy, and chemical preparation, and prepares a humic acid product with a high degree of depolymerization, effectively avoiding the huge carbon emissions and waste of organic resources in the traditional pyrometallurgical enrichment process of the germanium-rich lignite, and at the same time provides raw materials for the metallurgical industry and agriculture, with the advantages of less environmental pollution, high extraction efficiency, and low comprehensive cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for combined comprehensive utilization of germanium-rich lignite dressing and smelting, belonging to the technical field of comprehensive recovery and treatment of solid materials. Background Art

[0002] my country's proven lignite reserves amount to 130 billion tons, of which germanium resources account for about 8,000 to 10,000 tons. In the Ulan Tuga mining area of ​​Xilin Gol League, Inner Mongolia Autonomous Region alone, the proven germanium metal reserves have reached 3,332.45 tons, accounting for about 30% of the world's proven germanium reserves. It has become China's new "germanium capital" after Yunnan.

[0003] However, germanium-rich lignite has a low carbon content (50-70%), a high moisture content (15-60%), and although germanium is enriched, it is of low grade (about 200ppm). Efficient comprehensive treatment and utilization methods are still scarce. The existing mainstream process first uses high-temperature combustion oxidation by pyrolysis to pre-enrich germanium into smoke or slag, and then extracts germanium from the enriched material by chlorination and distillation. The process is long, energy-intensive, and reagent-intensive, and the germanium recovery rate is low. At the same time, each pyrolysis treatment of 1 ton of lignite will emit 1.83-2.57 tons of carbon dioxide, but the calorific value provided is less than 3,000 kcal, the utilization rate of carbonaceous resources is low, and the carbon emissions are high. These problems have seriously restricted the development of the germanium-rich lignite extraction industry. Therefore, it is urgent to develop low-carbon, economical, and efficient extraction, separation, and comprehensive utilization technologies that match the characteristics of key metallic germanium resources and carbonaceous resources in germanium-rich lignite.

[0004] At present, the extraction of germanium resources in lignite is mainly divided into two categories of technologies: wet processing and pyroprocessing. In addition, there are many related studies focusing on the secondary enrichment of germanium in germanium-containing soot, and the separation and recovery of lignite germanium extraction solution. The classic process for wet extraction of germanium-rich lignite is hydrochloric acid leaching-chlorination distillation. After the raw lignite is ground and slurried, a high-concentration hydrochloric acid solution with a concentration greater than 7 mol / L is added under heating conditions to directly leach and distill the germanium in the coal to obtain germanium tetrachloride. However, the hydrochloric acid concentration in this process is high, the consumption is large, the industrial cost is high, the hydrochloric acid concentration in the distillation residue is high, and there are many impurities such as arsenic and iron. It is difficult to reuse and difficult to handle, and it is not suitable for large-scale production. The pyroprocess extraction of germanium-rich lignite usually first uses high-temperature combustion by pyroprocessing to transfer germanium to smoke or slag, and then extracts germanium from the germanium concentrate by traditional chlorination distillation. In this process, germanium is easily wrapped by silicon dioxide to form a germanium-silicon co-solution, which increases the difficulty of subsequent chlorination distillation to extract germanium. In addition, many studies have been conducted on the secondary enrichment of germanium in germanium-containing fly ash, mainly including the classic chlorination distillation method, controlled atmosphere reduction volatilization method, fuming volatilization method, sodium roasting and neutralization method, etc. However, this type of method only recovers germanium resources, and the main organic matter in lignite is almost not utilized. Summary of the invention

[0005] In view of the problems of low germanium dissolution rate and low organic matter utilization rate in the recycling method of germanium-rich lignite in the prior art, the purpose of the present invention is to provide a method for the comprehensive utilization of germanium-rich lignite by beneficiation and smelting. The method combines the advantages of mineral processing, hydrometallurgy, and chemical preparation, and realizes the pre-activation of germanium-rich lignite through catalytic oxidation treatment, which can significantly improve the direct wet extraction rate of germanium in it. At the same time, compared with direct acid leaching, the amount of leaching agent and the heating leaching time are significantly reduced, and the activation, depolymerization degree and extraction rate of organic matter are improved. In addition, the present invention can greatly shorten the length of the comprehensive utilization technology route and effectively reduce the cost of the overall process.

[0006] In order to achieve the above technical objectives, the present invention provides a method for the combined comprehensive utilization of germanium-rich lignite beneficiation and smelting, comprising the following steps:

[0007] (1) After the germanium-rich lignite is beneficiated and graded, the muddy particles are removed, and the obtained oversize product is crushed and ground to obtain lignite raw material;

[0008] (2) mixing the lignite raw material, hydrogen peroxide and a solution containing ferrous ions and then subjecting them to catalytic pre-oxidation treatment, and obtaining an activated solution (a) and activated lignite solid after solid-liquid separation; the activated solution (a) is returned to the catalytic pre-oxidation treatment for recycling to achieve preliminary enrichment of germanium, thereby obtaining a preliminary enriched germanium-containing solution (a);

[0009] (3) The activated lignite solid is treated with nitric acid to extract germanium, and after solid-liquid separation, a germanium-containing solution (b) and a humic acid-rich solid product with a high degree of depolymerization are obtained; the germanium-containing solution (b) is returned to the germanium leaching treatment for recycling to achieve preliminary enrichment of germanium, thereby obtaining a preliminary enriched germanium-containing solution (b);

[0010] (4) The preliminarily enriched germanium-containing solution (a) and the preliminarily enriched germanium-containing solution (b) are adsorbed and eluted by an anion exchange resin separately or combined to obtain a germanium-rich solution.

[0011] The technical solution of the present invention organically combines the advantages of mineral processing, hydrometallurgy and chemical preparation, and realizes a significant increase in the one-time direct wet extraction rate of germanium and the degree of depolymerization of organic matter. Specifically, the principles of the present invention are as follows:

[0012] First of all, the germanium in the germanium-rich lignite mainly exists in the form of organic matter combined with germanium and trace germanium-containing minerals. Conventional mineral processing and enrichment methods are difficult to achieve its efficient enrichment. At the same time, considering that the raw germanium-rich lignite often contains a certain amount of mud, in which the germanium content is low and has a certain impact on subsequent extraction. Therefore, firstly, mineral processing and classification are used to remove the low-germanium mud part, which can reduce the impact of mud on the subsequent extraction process; at the same time, it can effectively reduce the ash content of the germanium-rich lignite, which is conducive to improving the purity of the subsequent humic acid product. And by crushing and grinding the above-screen product, it can help increase the specific surface area of ​​the lignite, which is conducive to improving the degree of subsequent pre-activation treatment.

[0013] Secondly, the germanium is extracted by a combined process of catalytic pre-oxidation treatment and nitric acid leaching treatment. The germanium in germanium-rich lignite is usually in the form of organic matter (Ge 4+ ) and germanium sulfide (Ge 2+ ) and other mineral forms, and the existing technology has limited release of germanium in germanium-rich lignite. The present invention has found through research that the direct wet extraction rate of germanium can be significantly improved by first activating with hydrogen peroxide and a solution containing ferrous ions, and then oxidizing and leaching with nitric acid, while significantly reducing the amount of leaching agent and the heating leaching time. The main principle is that under the catalysis of a certain number of ferrous ions, the continuous conversion of ferrous ions and trivalent iron ions can enable hydrogen peroxide to produce a large number of hydroxyl radicals. The free hydroxyl radicals in the solution can promote the breaking of some chemical bonds in the germanium-rich lignite particles, thereby breaking them up more thoroughly. At the same time, the organic matter bonded to germanium is further dissociated, which is more conducive to the subsequent oxidative leaching of nitric acid. The chemical reactions involved in the formation of hydroxyl radicals in the catalytic pre-oxidation treatment process of the present invention include the following:

[0014] H 2 O 2 +Fe 2+ →Fe 3+ +HO - + OH

[0015] RH+·OH→R·+H 2 O

[0016] R.+Fe 3+ →Fe 2+ + Oxidation products

[0017] H 2 O 2 + ·OH→HO 2 +H 2 O

[0018] Fe 2+ +·OH→Fe 3+ +HO -

[0019] Fe 3+ +H 2 O 2 →Fe 2+ +H + +HO 2 ·

[0020] Fe 3+ + HO 2 →Fe 2+ +H + +O 2

[0021] In addition, the catalytic pre-oxidation treatment and nitric acid oxidation process of the present invention can simultaneously promote the activation of organic matter in lignite and depolymerize high-molecular organic matter into humic acid, thereby improving the degree of activation and depolymerization of organic matter in germanium-rich lignite while extracting germanium, and producing a humic acid product with better structural properties.

[0022] In addition, the activation solution (a) and the germanium-containing solution (b) of the present invention can not only fully utilize the residual hydrogen peroxide, the ferrous ion-containing solution and the nitric acid through recycling, thereby reducing the amount of reagents used and the loss of germanium, but also this method can break the equilibrium system in the solution and reduce the difficulty of subsequent germanium removal through anion exchange resin.

[0023] If the germanium-rich lignite is not first graded and deslimed, and hydrogen peroxide and a solution containing ferrous ions are directly added for catalytic pre-oxidation treatment, the germanium-rich lignite will not be fully dissociated and cannot fully contact with the activation reagent, which will lead to a significant decrease in the primary leaching rate of germanium and the degree of depolymerization of organic matter.

[0024] As a preferred solution, the mineral processing and grading adopts a high-frequency fine screen with an aperture of 74 to 150 μm, and the crushing and grinding controls the particle size to be less than 150 μm. The raw germanium-rich lignite often contains a certain amount of mud, in which the germanium content is low and has a certain impact on subsequent extraction, and needs to be removed after mineral processing and grading. The present invention uses a fine screen with a high vibration frequency to effectively destroy the adhesion between the germanium-rich lignite and the mud particles, reduce the agglomeration force between fine-grained mud particles, and significantly improve the efficiency of mud removal. Within the range of sieve holes selected by the present invention, fine mud particles and coarser germanium-rich lignite can be effectively separated.

[0025] As a preferred solution, the molar ratio of hydrogen peroxide to the solution containing ferrous ions is (35-60):1, wherein the solution containing ferrous ions is calculated as ferrous ions. A key point of the present invention is to control the molar ratio of hydrogen peroxide to ferrous ions. 2+ When the addition amount is low, H 2 O 2 It cannot efficiently generate OH, but directly decomposes into H 2 O and O2 ; when Fe 2+ When the amount added increases, the ·OH generation efficiency is too high, and the excess ·OH reacts to generate H 2 O and O 2 , so that the lignite cannot be fully oxidized. And the molar ratio of the present invention is greatly different from that of the conventional Fenton reagent. The conventional Fenton reagent is mainly used for the depolymerization of organic matter in wastewater. 2 O 2 with Fe 2+ The mass ratio is usually between 1:1 and 10:1 (Technical Specifications for Wastewater Treatment Engineering by Fenton Oxidation Method (HJ1095-2020)), and the optimal treatment pH is around 2.0~3.0, with the purpose of completely decomposing organic matter. The proportion of hydrogen peroxide in the present invention is much larger than that of conventional Fenton reagents, and the concentration of ferrous ions in the activation system is low, so the ability of the generated hydrogen peroxide to catalyze the generation of hydroxyl radicals is relatively weak, so that the germanium-rich lignite can be pre-oxidized, but only the organic matter in the lignite is moderately depolymerized and oxidized to achieve the recovery of humic acid products with better structural properties; if the present invention adopts the high oxidizing ratio used by Fenton reagents, the organic matter in the present invention will be over-oxidized, the yield of humic acid in the organic matter will be reduced, and the subsequent solid-liquid separation process will also be difficult to carry out. It is further preferred to be (45~50):1, and it is further preferred to be 50:1.

[0026] As a preferred solution, the conditions for the catalytic pre-oxidation treatment are: liquid-to-solid ratio of (8-15):1, temperature of 20-25°C, time of 0.5-1h, and hydrogen peroxide concentration of 2.0-4.0 mol / L. More preferably, the liquid-to-solid ratio is (9-10):1, time of 0.5-0.6h, hydrogen peroxide concentration of 3-3.5 mol / L, and more preferably, the liquid-to-solid ratio is 10:1, time of 0.5h, and hydrogen peroxide concentration of 3 mol / L.

[0027] As a preferred solution, the conditions for the leaching of germanium are: nitric acid concentration of 0.7-1.2 mol / L, liquid-solid ratio of (8-15):1, leaching time of 0.5-1h, and temperature of 85-95°C. In the leaching stage of the present invention, lower nitric acid concentration, lower liquid-solid ratio, lower temperature or shorter leaching time will lead to insufficient leaching reaction of germanium-rich lignite, reducing the leaching rate of germanium. Excessive nitric acid concentration, liquid-solid ratio, temperature and time will increase the leaching cost, so it is necessary to complete the efficient leaching of germanium under appropriate conditions. It is further preferred that the nitric acid concentration is 0.8-0.9 mol / L, the liquid-solid ratio is (10-11):1, the leaching time is 0.5-0.6h, and the temperature is 90-95°C. It is further preferred that the nitric acid concentration is 0.8 mol / L, the liquid-solid ratio is 10:1, the leaching time is 0.5h, and the temperature is 90°C.

[0028] As a preferred solution, the number of cycles is 3 to 5. The present invention can extract and enrich germanium in lignite multiple times through cycles, reduce the loss of germanium in each processing link, and thus improve the overall recovery rate of germanium. When the number of cycles is too small, the residual reagent cannot be reused and the initial enrichment of germanium cannot be achieved.

[0029] As a preferred solution, the anion exchange resin is an anion exchange resin improved based on polyurethane resin, polyvinyl chloride resin or polypropylene resin. The several resins selected in the present invention all have good oxidation resistance and corrosion resistance, and can improve the stability of the overall extraction process of the present invention.

[0030] As a preferred solution, the humic acid yield in the humic acid-rich solid product with a high degree of depolymerization is greater than or equal to 45%, and the humic acid ultraviolet characteristic parameter E4 / E6 is greater than or equal to 9. E4 and E6 are the ratios of the ultraviolet absorbance of the humic acid solution at wavelengths of 465nm and 665nm under UV-vis, respectively, and this value is also called the humification index. The E4 / E6 value can be used to characterize the degree of depolymerization of humic acid, and a higher E4 / E6 value means a smaller molecular weight and a higher content of aliphatic compounds. The humic acid-rich solid product obtained by the combined process of metallurgy and smelting of the present invention has good humic acid structural characteristics and a higher yield, which is conducive to its application in fields with high activity requirements.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention effectively avoids the huge carbon emissions and waste of organic resources in the traditional pyrometallurgical enrichment process of germanium-rich lignite by combining mineral processing, hydrometallurgy and chemical preparation, while providing raw materials for the metallurgical industry and agriculture, with the advantages of less environmental pollution, high extraction efficiency and low comprehensive cost.

[0033] (2) The present invention achieves pre-activation of germanium-rich lignite through catalytic oxidation treatment, and the direct wet extraction rate of germanium can reach more than 80%. At the same time, compared with direct acid leaching, the amount of leaching agent and the heating leaching time are significantly reduced, and the activation, depolymerization degree and extraction rate of organic matter are improved. In addition, the present invention can greatly shorten the length of the comprehensive utilization technology route and effectively reduce the cost of the overall process.

[0034] (3) Through the catalytic pre-oxidation treatment and nitric acid oxidation process of the present invention, the activation of organic matter in lignite can be simultaneously promoted, and the high molecular organic matter can be depolymerized into humic acid, so that the degree of activation and depolymerization of organic matter in germanium-rich lignite can be improved while germanium is extracted, and a humic acid product with better structural properties is produced, wherein the humic acid yield in the humic acid-rich solid product is greater than or equal to 45%, and the humic acid ultraviolet characteristic parameter E4 / E6 is greater than or equal to 9.

[0035] (4) The present invention can achieve the pre-oxidation of germanium-rich lignite and the controllable degradation of organic matter by adopting a high molar ratio of hydrogen peroxide and ferrous ions.

[0036] (5) The activation solution (a) and the germanium-containing solution (b) of the present invention can achieve full utilization of residual hydrogen peroxide, ferrous ion-containing solution and nitric acid by recycling, thereby reducing the amount of reagents used and the loss of germanium. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the process flow of the combined comprehensive utilization of germanium-rich lignite beneficiation and smelting according to the present invention.

[0038] Figure 2 This is the UV-visible spectroscopic spectrum of humic acid before and after treatment with germanium-rich lignite in Example 1 of the present invention under the same test conditions, wherein: Figure 2 (a) unprocessed raw coal, Figure 2 (b) is the coal treated by catalytic pre-oxidation + nitric acid leaching according to the present invention. DETAILED DESCRIPTION

[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0040] Example 1

[0041] For a lignite in Yunnan that contains 210μg / g germanium, the raw coal is first graded using a high-frequency fine screen to remove muddy fine particles below -200 mesh (74μm), and the product on the screen is ground to less than 150μm as feed for subsequent processing. The above feed is taken to start catalytic activation pretreatment. During the reaction, the concentration of hydrogen peroxide is 3.0mol / L and the concentration of ferrous ions is 0.06mol / L (i.e., H 2 O 2 / Fe 2+ = 50:1), the reaction liquid-solid ratio is 10:1, the treatment time is 1h, the treatment temperature is room temperature, and after the catalytic activation pretreatment is completed, solid-liquid separation is performed to obtain an activated solution (a) and activated lignite solids. After the activated solution (a) is recycled 3 times, preliminary enrichment is achieved, and then the polyurethane-modified anion exchange resin is used to adsorb germanium, and then germanium is eluted and enriched to obtain a preliminary enriched germanium-containing solution (a); the activated lignite solids produced in the catalytic activation stage are used for nitric acid leaching treatment.

[0042] The activated lignite solid is reacted with 0.8 mol / L nitric acid solution to leach germanium, with a liquid-solid ratio of 10:1, the leaching temperature is controlled at 90°C, and the reaction time is 0.5 h. After the leaching is completed, solid-liquid separation is performed to obtain a germanium-containing solution (b) and a humic acid-rich solid product with a high degree of depolymerization. The germanium-containing solution (b) is recycled for 3 times to achieve preliminary enrichment of germanium, and an anion exchange resin modified with polypropylene resin is used to adsorb germanium, and then germanium is eluted and enriched to obtain a preliminary enriched germanium-containing solution (b). The preliminary enriched germanium-containing solution (a) and the preliminary enriched germanium-containing solution (b) are combined for subsequent germanium extraction.

[0043] Through the above-mentioned process, the direct wet extraction rate of germanium in germanium-rich lignite raw coal can reach 85.33%; the humic acid yield reaches more than 49.16%, and the humic acid ultraviolet characteristic parameter E4 / E6 reaches 9.54.

[0044] Figure 2 This is the UV-visible spectroscopic spectrum of humic acid before and after treatment with germanium-rich lignite in Example 1 of the present invention under the same test conditions, wherein: Figure 2 (a) unprocessed raw coal, Figure 2 (b) is the coal treated by catalytic pre-oxidation + nitric acid leaching of the present invention; as can be seen from the figure, after the treatment of the present invention, the ultraviolet characteristic parameters E4 / E6 of the humic acid obtained are significantly increased, and a product with a higher degree of depolymerization is obtained.

[0045] Example 2

[0046] The other conditions were the same as those in Example 1, except that the concentration of hydrogen peroxide was changed to 2.0 mol / L, and the concentration of ferrous ions was changed to 0.04 mol / L (maintaining the concentration of H 2 O 2 / Fe 2+ =50:1), other experimental parameters and steps were consistent with those in Example 1; ultimately, the one-time direct wet extraction rate of germanium was 80.34%, the yield of humic acid was 45.37%, and the degree of depolymerization of humic acid E4 / E6 was 9.06.

[0047] Compared with Example 1, when the liquid-to-solid ratio in this embodiment is the same, the concentration of hydrogen peroxide changes, the concentration of ferrous ions also changes, and the concentration of hydroxyl radicals in the solution also changes, thereby affecting the catalytic oxidation of germanium-rich lignite and affecting the final extraction rate and yield.

[0048] Example 3

[0049] Other conditions were consistent with those in Example 1, except that the concentration of nitric acid was changed to 1.2 mol / L, and other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 86.50%, the yield of humic acid was 47.25%, and the degree of depolymerization of humic acid E4 / E6 was 9.13.

[0050] Example 4

[0051] The other conditions were consistent with those in Example 1, except that the liquid-solid ratio of the nitric acid leaching solution was changed to 12.5:1, and the other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 80.96%, the yield of humic acid was 47.06%, and the degree of depolymerization of humic acid E4 / E6 was 9.28.

[0052] Example 5

[0053] For a lignite in Yunnan that contains 210μg / g germanium, the raw coal is first graded using a high-frequency fine screen to remove muddy fine particles below 150 mesh (100μm), and the product on the screen is ground to less than 150μm as feed for subsequent processing. The above feed is taken to start catalytic activation pretreatment. During the reaction, the hydrogen peroxide concentration is 3.0mol / L and the ferrous ion concentration is 0.06mol / L (i.e., H 2 O 2 / Fe 2+ = 50:1), the reaction liquid-solid ratio is 9:1, the treatment time is 0.6h, and the treatment temperature is room temperature. After the catalytic activation pretreatment is completed, solid-liquid separation is performed to obtain an activated solution (a) and activated lignite solids. After the activated solution (a) is recycled 4 times, preliminary enrichment is achieved, and then polyurethane-modified anion exchange resin is used to adsorb germanium, and then germanium is eluted and enriched to obtain a preliminary enriched germanium-containing solution (a); the activated lignite solids produced in the catalytic activation stage are used for nitric acid leaching treatment.

[0054] The activated lignite solid is reacted with 0.8 mol / L nitric acid solution to leach germanium, with a liquid-solid ratio of 11:1, the leaching temperature is controlled at 92°C, and the reaction time is 0.6h. After the leaching is completed, solid-liquid separation is performed to obtain a germanium-containing solution (b) and a humic acid-rich solid product with a high degree of depolymerization. The germanium-containing solution (b) is recycled 4 times to achieve preliminary enrichment of germanium, and an anion exchange resin modified with polypropylene resin is used to adsorb germanium, and then germanium is eluted and enriched to obtain a preliminary enriched germanium-containing solution (b). The preliminary enriched germanium-containing solution (a) and the preliminary enriched germanium-containing solution (b) are combined for subsequent germanium extraction.

[0055] Through the above-mentioned process, the direct wet extraction rate of germanium in germanium-rich lignite raw coal can reach 84.61%; the humic acid yield reaches more than 48.02%, and the humic acid ultraviolet characteristic parameter E4 / E6 reaches 9.33.

[0056] Comparative Example 1

[0057] Other conditions were consistent with those in Example 1, except that the raw coal was not subjected to high-frequency fine screening and classification, and the mud fine particles below -200 mesh (74 μm) were not removed. Other experimental parameters and steps were consistent with those in Example 1. Finally, the recovery rate of germanium was 79.58%, the yield of humic acid was 43.07%, and the degree of depolymerization of humic acid E4 / E6 was 6.93.

[0058] Comparative Example 2

[0059] The other conditions were the same as those in Example 1, except that the concentration of ferrous ions was changed to 0.04 mol / L (i.e., H 2 O 2 / Fe 2+ = 75:1), other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 64.00%, the yield of humic acid was 35.64%, and the degree of depolymerization of humic acid E4 / E6 was 7.42.

[0060] Comparative Example 3

[0061] The other conditions were the same as those in Example 1, except that the concentration of ferrous ions was changed to 0.12 mol / L (i.e., H 2 O 2 / Fe 2+ = 25:1), other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 67.26%, the yield of humic acid was 32.29%, and the degree of depolymerization of humic acid E4 / E6 was 7.17.

[0062] Comparative Example 4

[0063] The other conditions were consistent with those in Example 1, except that the concentration of nitric acid was changed to 0.6 mol / L, and the other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 64.34%, the yield of humic acid was 37.94%, and the degree of depolymerization of humic acid E4 / E6 was 8.25.

[0064] Comparative Example 5

[0065] The other conditions were consistent with those in Example 1, except that the nitric acid leaching temperature was changed to 70°C, and the other experimental parameters and steps were consistent with those in Example 1; ultimately, the recovery rate of germanium was 40.06%, the yield of humic acid was 39.26%, and the degree of depolymerization of humic acid E4 / E6 was 8.74.

[0066] Comparative Example 6

[0067] The other conditions were the same as those in Example 1, except that the feed was not subjected to catalytic pre-oxidation treatment but was directly subjected to leaching reaction using 1 mol / L nitric acid solution, and the other experimental parameters and steps were the same as those in Example 1; ultimately, the recovery rate of germanium was 57.95%, the yield of humic acid was 43.19%, and the degree of depolymerization of humic acid E4 / E6 was 9.06.

[0068] The above are only some of the preferred specific embodiments of the present invention and some of the cases in the process of technical exploration of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for combined comprehensive utilization of germanium-rich lignite dressing and smelting, characterized in that: The following steps are involved: (1) After the germanium-rich lignite is beneficiated and graded, the muddy particles are removed, and the obtained oversize product is crushed and ground to obtain lignite raw material; (2) mixing the lignite raw material, hydrogen peroxide and a solution containing ferrous ions and then subjecting them to catalytic pre-oxidation treatment, and obtaining an activated solution (a) and activated lignite solid after solid-liquid separation; the activated solution (a) is returned to the catalytic pre-oxidation treatment for recycling to achieve preliminary enrichment of germanium, thereby obtaining a preliminary enriched germanium-containing solution (a); (3) The activated lignite solid is treated with nitric acid to extract germanium, and after solid-liquid separation, a germanium-containing solution (b) and a humic acid-rich solid product with a high degree of depolymerization are obtained; the germanium-containing solution (b) is returned to the germanium leaching treatment for recycling to achieve preliminary enrichment of germanium, thereby obtaining a preliminary enriched germanium-containing solution (b); (4) the preliminarily enriched germanium-containing solution (a) and the preliminarily enriched germanium-containing solution (b) are separately or combined and then adsorbed and eluted by an anion exchange resin to obtain a germanium-rich solution; The molar ratio of the hydrogen peroxide to the solution containing ferrous ions is (35-60):1, wherein the solution containing ferrous ions is calculated based on ferrous ions.

2. The method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 1, characterized in that: The ore dressing and grading adopts a high-frequency fine screen with an aperture of 74-150 μm, and the crushing and grinding controls the particle size to be below 150 μm.

3. A method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 1 or 2, characterized in that: The molar ratio of the hydrogen peroxide to the solution containing ferrous ions is (45-50):1, wherein the solution containing ferrous ions is calculated based on ferrous ions.

4. The method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 1, characterized in that: The conditions of the catalytic pre-oxidation treatment are: liquid-to-solid ratio of (8-15):1, temperature of 20-25°C, time of 0.5-1h, and concentration of hydrogen peroxide of 2.0-4.0 mol / L.

5. A method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 1, 2 or 4, characterized in that: The conditions for the germanium leaching treatment are: nitric acid concentration of 0.7-1.2 mol / L, liquid-to-solid ratio of (8-15):1, leaching time of 0.5-1h, and temperature of 85-95°C.

6. The method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 5, characterized in that: The number of times of recycling is 3 to 5 times.

7. The method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 1, characterized in that: The anion exchange resin is an anion exchange resin improved based on polyurethane resin, polyvinyl chloride resin or polypropylene resin.

8. The method for combined comprehensive utilization of germanium-rich lignite dressing and smelting according to claim 7, characterized in that: The humic acid yield of the humic acid-rich solid product with a high degree of depolymerization is greater than or equal to 45%, and the humic acid ultraviolet characteristic parameter E4 / E6 is greater than or equal to 9.

Citation Information

Patent Citations

  • Method for recycling uranium from uranium extraction coal residue with wet method

    CN101619397A

  • Method for enriching germanium from germanium-bearing lignite soot

    CN109402409A